2013
DOI: 10.1111/vop.12119
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of alfaxalone and propofol on intraocular pressure in healthy dogs

Abstract: These data show a potentially clinically significant increase in IOP following induction with propofol or alfaxalone, but no difference between agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 28 publications
0
39
3
Order By: Relevance
“…This difference could be explained by the simultaneous use of premedication drugs (acepromazine-hydromorphone), which could have induced pharmacologic or pharmacokinetic interactions. Furthermore, the difference could be explained by the different duration of both studies; the present study lasted 30 minutes, while in Hasiuk and others (2013), IOP measurements were stopped right after orotracheal intubation. This manoeuvre might be potentially associated with a transient IOP elevation (Hofmeister and others 2006).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This difference could be explained by the simultaneous use of premedication drugs (acepromazine-hydromorphone), which could have induced pharmacologic or pharmacokinetic interactions. Furthermore, the difference could be explained by the different duration of both studies; the present study lasted 30 minutes, while in Hasiuk and others (2013), IOP measurements were stopped right after orotracheal intubation. This manoeuvre might be potentially associated with a transient IOP elevation (Hofmeister and others 2006).…”
Section: Discussionmentioning
confidence: 85%
“…A normal to slightly lower than normal IOP, a central and fixed globe, and physiological tear production are desirable before and during ocular surgery (Murphy 1985, Herring and others 2000, Gross and Giuliano 2007). In dogs, these ocular parameters have been investigated after the administration of methoxyflurane (Vassilieff 1976), flumazenil (Artru 1991), medetomidine (Verbruggen and others 2000, Wallin-Håkanson and Wallin-Håkanson 2001), sevoflurane, desflurane (Almeida and others 2004), nitrous oxide (Almeida and others 2008), thiopental (Hofmeister and others 2008), propofol (Batista and others 2000, Hofmeister and others 2008, 2009, Hasiuk and others 2013), ketamine–midazolam (Ghaffari and others 2010), isoflurane (Shepard and others 2011) and dexmedetomidine (Artigas and others 2012). To the authors’ knowledge, the effect of a single intravenous bolus of alfaxalone on ocular parameters has not been previously investigated in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…In three different studies using TonoVet ® , the mean IOP in Beagles was determined as 14.3 ± 2.4 mmHg (4), 15.2 ± 1.0 mmHg (18), and 15.6 ± 2.0 and 17.1 ± 2.4 mmHg (20). In studies in which measurements were made with TonoVet ® and many mix breeds were used as study material, various IOP values were recorded: 15.9 ± 2.1 mmHg and 16.9 ± 3.4 mmHg (3); 16.0 ± 3.2 to 18.3 ± 1.8 mm Hg (17); 14.2 ± 3.6 to 17.7 ± 3.1 mmHg (16) and 15.5 ± 2.7 to 15.7 ± 2.8 mmHg (9). In the present study, regardless of age, sex, and eye side, the mean IOP value for Kangal dogs measured with TonoVet ® was 17.63 ± 3.34 mmHg, which was higher than mean IOPs obtained in three studies on Beagles and similar to mean IOPs in other studies in which different breeds were used (3,9,16,17).…”
Section: Methodsmentioning
confidence: 99%
“…In studies in which measurements were made with TonoVet ® and many mix breeds were used as study material, various IOP values were recorded: 15.9 ± 2.1 mmHg and 16.9 ± 3.4 mmHg (3); 16.0 ± 3.2 to 18.3 ± 1.8 mm Hg (17); 14.2 ± 3.6 to 17.7 ± 3.1 mmHg (16) and 15.5 ± 2.7 to 15.7 ± 2.8 mmHg (9). In the present study, regardless of age, sex, and eye side, the mean IOP value for Kangal dogs measured with TonoVet ® was 17.63 ± 3.34 mmHg, which was higher than mean IOPs obtained in three studies on Beagles and similar to mean IOPs in other studies in which different breeds were used (3,9,16,17). With regard to studies using applanation tonometers, mean IOPs obtained with Tono-Pen XL ® for Beagles ranged from 12.7 ± 0.8 to 15.3 ± 1.7 mmHg in one study (10) and was found to be 15.2 ± 2.2 mmHg in another (19).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the success of ophthalmic procedures may depend on their control before, during and after the surgery (Gross and Giuliano 2007, Hasiuk and others 2014). …”
Section: Introductionmentioning
confidence: 99%